2021
DOI: 10.1038/s41598-021-84763-z
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Tatun volcanic plumbing structure induced by post-collisional extension of Taiwan mountain belt

Abstract: The Tatun Volcanic Group (TVG) is proximal to the metropolis of Taipei City (population of ca. 7 million) and has long been a major concern due to the potential risks from volcanic activity to the population and critical infrastructure. While the TVG has been previously considered a dormant or extinct volcano, recent evidence suggests a much younger age of the last eruption event (~ 6000 years) and possible existence of a magma reservoir beneath the TVG. However, the location, dimension, and detailed geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…3). Interestingly, previous travel-time tomographic studies have consistently reported high-velocity anomalies in the same region 12,31 . The coexistence of these high-V and high-Q anomalies suggests a potential correlation with the exhumation of metamorphic slate and argillite belts during the mountain-building process.…”
Section: Low Attenuation Anomalies (High Q) and Serpentinizationmentioning
confidence: 80%
See 3 more Smart Citations
“…3). Interestingly, previous travel-time tomographic studies have consistently reported high-velocity anomalies in the same region 12,31 . The coexistence of these high-V and high-Q anomalies suggests a potential correlation with the exhumation of metamorphic slate and argillite belts during the mountain-building process.…”
Section: Low Attenuation Anomalies (High Q) and Serpentinizationmentioning
confidence: 80%
“…While we acknowledge the possibility that low- Q anomalies could be attributed to strong scattering attenuation, as observed in other volcanic regions 68 , 69 , a recent waveform modeling study 46 supports the hypothesis of active hydrothermal events in the TVG region favoring fluid-related contributions. Moreover, the existence of a magma reservoir beneath the TVG region remains plausible but may be situated at greater depths, as suggested by recent tomographic investigations 12 . These deeper magma reservoirs could serve as potential heat sources for the shallower hydrothermal system.…”
Section: Lateral Variations Of Attenuation In Northern Taiwanmentioning
confidence: 82%
See 2 more Smart Citations
“…This slow anomaly might be related to the magmatic structure of the TVG. Few recent studies have presented evidence indicating the presence of a mid‐crustal magma body associated with the Tatun Volcano (Huang et al., 2021; Lin, 2016). The relative shallow slow anomaly we observed might be related to the remnant magmatic materials left from previous eruptions, or part of the still active magmatic system.…”
Section: Discussionmentioning
confidence: 99%